PENGARUH LEVERAGE, MODAL KERJA, EFISIENSI PERUSAHAAN DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS BUMN YANG TERDAFTAR DI BEI - Muhammad Ikram; Zaida Rizqi Zainul (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2023)
This study aims to determine the effect of leverage, working capital, company efficiency and company size on profitability in state-owned enterprises (BUMN) listed on the Indonesia Stock Exchange (IDX). This study uses panel data with 20 state-owned companies listed on the Indonesia Stock Exchange (IDX) from the 2016-2021 period. The analytical method used is panel data regression analysis using Eviews 10. The sampling technique used is purposive sampling with multiple linear regression data analysis using the fixed effect model. The results of this study partially show that leverage and company efficiency have a positive and significant effect on profitability (ROE and EPS), working capital has a positive and insignificant effect on profitability (ROE) and has a negative and insignificant effect on profitability (EPS), firm size has a positive and insignificant effect on profitability (EPS). negative and not significant to profitability (ROE and EPS). The results of the study simultaneously show that Leverage, Working Capital, Company Efficiency and Company Size Influence on Profitability of State-Owned Enterprises (BUMN) Listed on the Indonesia Stock Exchange (IDX).